2010
DOI: 10.1242/jcs.053496
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional organization of promyelocytic leukemia nuclear bodies

Abstract: SummaryPromyelocytic leukemia nuclear bodies (PML-NBs) are mobile subnuclear organelles formed by PML and Sp100 protein. They have been reported to have a role in transcription, DNA replication and repair, telomere lengthening, cell cycle control and tumor suppression. We have conducted high-resolution 4Pi fluorescence laser-scanning microscopy studies complemented with correlative electron microscopy and investigations of the accessibility of the PML-NB subcompartment. During interphase PML-NBs adopt a spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 66 publications
14
102
0
1
Order By: Relevance
“…In line with a previous study (Potts and Yu, 2007), knockdown of these proteins reduced APB formation in our RNAi screen. The relevance of sumoylation of shelterin and PML-NB components for PML-NB and APB formation has been described in a number of previous studies (Brouwer et al, 2009;Chung et al, 2011;Hattersley et al, 2011;Lang et al, 2010;Potts and Yu, 2007;Yu et al, 2010). Here, we additionally found that MMS21 knockdown increased TRF2 binding to telomeres in APBs, whereas knockdown of the SUMO protease SENP6 resulted in a decrease.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In line with a previous study (Potts and Yu, 2007), knockdown of these proteins reduced APB formation in our RNAi screen. The relevance of sumoylation of shelterin and PML-NB components for PML-NB and APB formation has been described in a number of previous studies (Brouwer et al, 2009;Chung et al, 2011;Hattersley et al, 2011;Lang et al, 2010;Potts and Yu, 2007;Yu et al, 2010). Here, we additionally found that MMS21 knockdown increased TRF2 binding to telomeres in APBs, whereas knockdown of the SUMO protease SENP6 resulted in a decrease.…”
Section: Discussionsupporting
confidence: 75%
“…2G). PML enrichment upon HP1γ recruitment could be due to SUMO-mediated interactions as discussed previously (Lang et al, 2010) or could occur through SP100 (Seeler et al, 1998), a known interaction partner of PML. Notably, PML enrichment was accompanied by the induction of repair-associated DNA synthesis, as concluded from the increased levels of the phosphorylated histone variant H2A.X (γH2A.X) and of incorporated 5-bromo-2'-deoxyuridine (BrdU) (Fig.…”
Section: An Rnai Screen With Automated 3d Image Analysis Identifies 2mentioning
confidence: 83%
“…7,[25][26][27] Immunoelectron or high resolution confocal analyses indicate that the PML protein forms the outer shell, whereas partner proteins are concentrated in the inner core. 26,[28][29][30] The outer PML shell is associated with the nuclear matrix, a loosely defined, insoluble nuclear scaffold that is resistant to nuclease and high salt extraction and thought to support nuclear organization and compartmentalization. 31,32 Over the course of many years, a growing number of functionally distinct proteins and enzymes were shown to be recruited into PML NBs, notably p53 and many of its regulatory enzymes.…”
Section: A Brief Historymentioning
confidence: 99%
“…ND10 structures form and reform in response to stress. They consist of an outer shell composed of PML, a set of constant proteins (e.g., CBP, Daxx, SP100 nuclear antigen), and various other proteins depending on the particular stress or function of the ND10 bodies (1)(2)(3)(4)(5)(6)(7). ND10 bodies have drawn attention recently, in large part because of increasing evidence suggesting that they sense and respond to infection (5,8).…”
mentioning
confidence: 99%